Positioning for advantage techniques and strategies to grow brand value - Whitler, Kimberly A. (Columbia University Press, 2021)
"Most of us have an intuitive sense of superior branding. We prefer to purchase brands we find distinctive-that deliver on some important, relevant dimension better than other brands. These brands have typically achieved positional advantage. Yet few professionals have had the formal training that goes beyond marketing theory to bridge the "theory-doing gap"-providing specific tools that can be used to create brands that attain positional advantage in the marketplace. Positioning for Advantage is a comprehensive how-to guide for creating, building, and executing effective brand strategies. Kimberly A. Whitler identifies essential marketing strategy techniques and moves through the major stages of positioning a brand to achieve in-market advantage. Introducing seven tools-from strategic positioning to strategy mapping to influencer maps-Whitler provides templates, frameworks, and step-by-step processes to build and manage growth brands that achieve positional advantage. This book presents real-world scenarios, helping readers activate the tools through practice to increase skill in creating brands that achieve positional advantage. Brimming with insights for students and professionals alike, Positioning for Advantage helps aspiring C-level leaders understand not only what superior branding looks like but also how to make it come to life"--